2019
DOI: 10.3390/w11091882
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic and Soil Biodiversity Characterization in an Active Landslide

Abstract: Landslides are common in the Northern Apennines (Italy) and their resulting changes in soil structure affect edaphic fauna biodiversity, whose activity has concurrent impacts on soil structural stability and water-holding capacity. The aim of this study was to characterise landslide evolution and assess potential relationships between its hydrogeological features and soil fauna. The landforms of the study area, located in the River Taro valley, were mapped and the hydraulic head fluctuations and groundwater el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
(45 reference statements)
0
5
0
3
Order By: Relevance
“…Their feeding habits are probably related to mycorrhizae, from which they take nutrients through their styliform buccal pieces [16]. There are very few studies on the use of this group as an indicator of soil health and, when considered, it is discussed in a wider approach aimed at studying the whole soil microarthropod community [17][18][19]. Moreover, Socarrás [14] observed that they inhabit deep strata, so that they are not affected by alterations occurring in higher ones.…”
Section: Introductionmentioning
confidence: 99%
“…Their feeding habits are probably related to mycorrhizae, from which they take nutrients through their styliform buccal pieces [16]. There are very few studies on the use of this group as an indicator of soil health and, when considered, it is discussed in a wider approach aimed at studying the whole soil microarthropod community [17][18][19]. Moreover, Socarrás [14] observed that they inhabit deep strata, so that they are not affected by alterations occurring in higher ones.…”
Section: Introductionmentioning
confidence: 99%
“…Em relação à família Formicidae, a mesma constitui-se um dos maiores grupos de invertebrados das florestas tropicais, onde sua riqueza e diversidade de espécies tendem a aumentar de acordo com a complexidade dos ambientes, devido a maior disponibilidade de nichos presentes (Rocha et al, 2015). No solo atuam em conjunto na redistribuição de partículas da matéria orgânica, melhorando a infiltração de água no solo pelo aumento da porosidade e aeração (Machado et al, 2015;Remelli et al, 2019). Devido à grande diversidade de gêneros, hábitos alimentares e de forrageamento, podem refletir em grandes densidades amostradas nos ambientes (Danozo, 2017).…”
Section: Methodsunclassified
“…A fauna edáfica é um importante componente terrestre que desempenha no solo importantes funções ecológicas, formando uma complexa teia trófica em cuja base estão as raízes, serapilheira e a matéria orgânica do solo (Bardgette Van Der Putter, 2014;Brown et al, 2015). A comunidade de organismos edáficos está diretamente relacionada à ciclagem de nutrientes, a dinâmica de decomposição da matéria orgânica, na melhoria de atributos físicos como agregação, porosidade e taxa de infiltração de água, fluxo de energia, regulação de plantas e outros organismos, além de auxiliar na polinização e dispersão de sementes (Brown et al, 2015;Remelli et al, 2019;Martins et al, 2020). Considerando suas funcionalidades, a fauna edáfica tem sido utilizada como bioindicadora de qualidade do solo por sua extrema sensibilidade as perturbações antrópicas e por estarem correlacionados com inúmeras funções do solo, sendo de fácil estimativa e boa representação do ambiente que promovem (Baretta et al, 2011;Coyle et al, 2017;Rohyany, 2020), inclusive podendo refletir e caracterizar um ecossistema alterado (e.g.…”
Section: Introductionunclassified
“…A nivel de paisaje, los deslizamientos actúan como factores de perturbación y tienen un papel fundamental en la impronta de la estructura de la vegetación al crear hábitats discontinuos remanentes de pocos árboles aislados, rodeados de áreas de remoción; esto garantiza un aumento de la diversidad espacial y funcional (efecto positivo) (Grau 2005;Alexandrowicz and Margielewski 2010;Pop and Chitu 2013). Asimismo, los cambios en la topografía, en las propiedades del suelo y en la vegetación dan forma a una brecha entre los deslizamientos y el hábitat circundante, con posibilidad de asentamiento para diferentes comunidades del suelo (Remelli et al 2019). Sin embargo, el aumento de la heterogeneidad estructural no siempre se percibe como beneficioso para mantener una biodiversidad rica, ya que puede facilitar la instalación de especies exóticas invasoras y disminuir la diversidad.…”
Section: R������unclassified